(untitled) (Medico Legal Update, 2021)
Death due to burns is a major public health problem worldwide. Most cases occur in middle and low-income countries. In India, deaths due to burns are commoner in women than in men. Fire is easily available weapon for suicide and homicide and it can also cause accidental deaths. Death due to burns in newly married female is a common incident in our country and major fraction of such deaths happen as a result of dowry harassment or killing for not giving dowry. Our study aimed to identify some of the epidemiological factors in deaths due to burns in newly married females in and around Pondicherry. Out of 48 cases during the study period, 24 victims were in the age group of 22-25 years and 26 women died within 3 years of marriage. The majority of the cases occurred in less educated and homemaker wives and were living in a joint family. Major reasons or motive behind deaths were dowry harassment and torture, and quarrel with husband or inlaws. The most common manner of such deaths was suicidal followed by accidental.